2022
DOI: 10.3201/eid2813.220780
|View full text |Cite
|
Sign up to set email alerts
|

Determining Gaps in Publicly Shared SARS-CoV-2 Genomic Surveillance Data by Analysis of Global Submissions

Abstract: Viral genomic surveillance has been a critical source of information during the COVID-19 pandemic, but publicly available data can be sparse, concentrated in wealthy countries, and often made public weeks or months after collection. We used publicly available viral genomic surveillance data submitted to GISAID and GenBank to examine sequencing coverage and lag time to submission during 2020–2021. We compared publicly submitted sequences by country with reported infection rates and population and also examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…We restricted our analysis to HICs because more accessible testing in those countries likely provides a more accurate assessment of the case and death burdens ( 15 , 16 ). We included HICs that reported > 200 SARS-CoV-2 sequences during the full period of interest (April 1, 2020–November 30, 2021) and > 20 Delta sequences in the first month of Delta dominance.…”
Section: Methodsmentioning
confidence: 99%
“…We restricted our analysis to HICs because more accessible testing in those countries likely provides a more accurate assessment of the case and death burdens ( 15 , 16 ). We included HICs that reported > 200 SARS-CoV-2 sequences during the full period of interest (April 1, 2020–November 30, 2021) and > 20 Delta sequences in the first month of Delta dominance.…”
Section: Methodsmentioning
confidence: 99%
“…This proved particularly problematic in low-income settings, for example in many parts of Africa, where a lack of existing sequencing infrastructure and expertise in genome analyses hindered the management and initial response to COVID-19 (22). Global analysis of viral sequence data deposited in public repositories has allowed quantitative assessments of national SARS-CoV-2 genomic surveillance programs in terms of case coverage, timeliness of reporting, and completeness of data sharing, broken down by sampling strategies and sequencing technology (28)(29)(30). The analysis has shown that, during the first 2 years of the pandemic, the SARS-CoV-2 genomic surveillance landscape displayed marked heterogeneity of outputs by country and economic income level.…”
Section: Weaknessesmentioning
confidence: 99%
“…The analysis has shown that, during the first 2 years of the pandemic, the SARS-CoV-2 genomic surveillance landscape displayed marked heterogeneity of outputs by country and economic income level. While 78% of high-income countries (HICs) sequenced >0.5% of reported COVID-19 cases, only 42% of low-and middle-income countries (LMICs) achieved that coverage level (29). The mean sequencing coverage ranged by region, from 0.1% in the Eastern Mediterranean region to 3.4% in Europe (28).…”
Section: Weaknessesmentioning
confidence: 99%
“…Surveys provided key data on SARS-CoV-2 cases in Pakistan ( 8 ) and Malawi ( 9 ). Ohlsen et al found international disparities in SARS-CoV-2 sequencing capacity and timeliness while viral genomic surveillance coverage increased globally ( 10 ). Smith-Sreen et al compared 3 waves of the pandemic in 10 countries in southern Africa ( 11 ).…”
Section: Surveillance Information and Laboratory Systemsmentioning
confidence: 99%